Convergence analysis of regional literacy rates in India - Jeet Saha; Zafar Iqubal (Social Sciences and Humanities Open)
The literacy rate is a crucial prerequisite for individual empowerment. Approximately one-fourth of the population in India is still illiterate, which is a significant number given the country's population size. However, wide disparities in literacy rates persist across Indian states. This study aims to examine whether these differences in literacy rates across states are narrowing over time. To investigate this, we conduct a convergence analysis using a non-linear factor dynamic model. We analyse the convergence patterns of rural, urban, and total literacy rates and find evidence that Indian states are converging in terms of rural and total literacy rates. However, in the case of urban literacy, two distinct convergence clubs have emerged. Our analysis reveals that rural literacy in India has improved more rapidly than urban literacy in recent years, and the strong convergence observed in rural areas, where the majority of the population resides, is the primary driver of overall convergence. The key implication of our findings is that regional disparities in literacy are declining in India, with states that initially had low literacy rates gradually catching up with those that had higher rates.